The form of a singular decree in the canonical legal order (Can. 51 CIC) - DZIERŻON, GINTER (Prawo Kanoniczne, 2017)
The author of the presented article carried out a thorough interpretation of can. 51 CIC. e focus of his attention were 2 issues: the question of a writ- ten form of a decree and the problem of motivation behind it. According to his analysis, the obligation to issue a decree in writing is not obvious. The disposition included in can. 51 CICI does not accord with the criteria determined in can. 10 CIC which concerns invalidating and disqualifying laws. e author proved that the canonical legal order includes regulations concerning the written form of decrees which meet the conditions dened in can. 10 CIC. Such a legislative mechanism was used in can. 474 CIC according to which acts of the curia in order to have juridic eect must be signed by the ordinary. e author believes that the written form guaran- tees the validity and security of administrative acts and is necessary for evidential purposes. Another focus of the author’s attention was the question of motivation of a decree. As he believes, from the perspective of administrative practice, the most appropriate solution would be for every issued act to include its motivation. In consequence, the addressee of an act would learn about both legal and actual reasons behind a particular decision. The author proved that not meeting the requirement concerning the motivation of a decree does not result in its invalidity but makes it illegal since the norm included in can. 51 CIC does not meet the conditions codi- ed in can. 10 CIC.